2010
DOI: 10.6028/jres.115.018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of nanoparticles of calcium phosphates with various Ca/P ratios

Abstract: This study aimed at preparing and studying the properties of nanoparticles of calcium phosphate (nCaP) with Ca/P ratios ranging from 1.0 to 1.67 using a spray-drying technique. Micro-structural analyses suggested that the nCaPs with Ca/P ratios of 1.67 to 1.33 were nano-sized amorphous calcium phosphate (ACP) containing varying amounts of acid phosphate and carbonate. The nCaP with Ca/P ratio of 1 contained only nano-sized low crystalline dicalcium phosphate (DCP). BET measurements of the nCaPs showed specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 34 publications
5
62
0
2
Order By: Relevance
“…Previously published studies have reported that a characteristic mass loss is observed in the TGA spectra of calcium phosphate nanoparticles at both 200°C and 400°C that corresponds to loss of adsorbed water and pyrophosphate formation. 24 The TGA analysis of chitosan-sodium tripolyphosphate nanoparticles was performed in another study, and it was reported that the maximum loss of weight occurs at the temperature range of 225°C-530°C. 25 Meanwhile, studies have also reported that the maximum weight loss in TGA spectra of alginate is observed at 400°C.…”
Section: +2mentioning
confidence: 99%
“…Previously published studies have reported that a characteristic mass loss is observed in the TGA spectra of calcium phosphate nanoparticles at both 200°C and 400°C that corresponds to loss of adsorbed water and pyrophosphate formation. 24 The TGA analysis of chitosan-sodium tripolyphosphate nanoparticles was performed in another study, and it was reported that the maximum loss of weight occurs at the temperature range of 225°C-530°C. 25 Meanwhile, studies have also reported that the maximum weight loss in TGA spectra of alginate is observed at 400°C.…”
Section: +2mentioning
confidence: 99%
“…Such enhancers include aliphatic acids, fatty acids, esters, alcohols, oils and terpens 1 and also variety of nanoparticle including elemental or polymeric nanoparticles [7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…To address these problems, the Maryland Bridge was developed in the late 1970s; It was easy to place and strong, since it does not use the retention holes in the retainers. However, it also had disadvantages: a complicated electrode etching procedure is required and can only be used with nickel-chromium alloys [14,15].…”
Section: An Example Of Macromechanical Retention Is What Was Donementioning
confidence: 99%